Flick Flack Training Tool for Beginner Athletes PERSANI Medan - Novita Novita; Yasmine Nadia Khairunisa (UNIB Press, 2021)
Gymnastics is a body exercise on the floor or on a device designed to increase endurance, strength, flexibility, agility, coordination and self-control. One of them is floor exercise, this exercise also has various kinds of movements that are not easy to do, for example, the movement flick flack. Beginner athletes in PERSANI, Medan City have not mastered the movement properly flick flack due to limited tools and costs from PERSANI so that the coach has to innovate with existing tools. The population in this study were 9 Siahaanathletes Gymnastic Club, 5 Windy's Gymnastic Clubathletes, 2athletesathlete Star Kids Gymnastic Club and 1 QA Gymnastic Club in 2020. The Training tool was flick flack validated first by 9 experts, 3 experts in in sports, 3 experts in the field of equipment / media, 3 experts in the field of coaches, where the average percentage value of validity is 81.8%, thus according to the experts they get the